Magnetically tunable spontaneous superradiance from mesoscopic perovskite emitter clusters - He, Ruihua (2023)
Perovskite emitters are promising materials as next-generation optical sources due to their low fabrication cost and high quantum yield. In particular, the superradiant emission from a few coherently coupled perovskite emitters can be used to produce a bright entangled photon source. Here, we report the observation of superradiance from mesoscopic (<55) CsPbBr3 perovskite emitters, which have a much smaller ensemble size than the previously reported results (>106 emitters). The superradiance is spontaneously generated by off-resonance excitation and detected by time-resolved photoluminescence and second-order photon correlation measurements. We observed a remarkable magnetic tunability of the superradiant photon bunching, indicating a magnetic field-induced decoherence process. The experimental results can be well explained using a theoretical framework based on the microscopic master equation. Our findings shed light on the superradiance mechanism in perovskite emitters and enable low-cost quantum light sources based on perovskite.